Monitoring mangrove crab Ucides cordatus Linnaeus, 1763 (Crustacea: Ucididae) landing in the Parnaíba River Delta: fishing characteristics, social and economic aspects - Fogaça,Fabiola Helena dos Santos (2018)
Abstract The century-old mangrove crab Ucides cordatus Linnaeus, 1763 harvesting is a traditional activity of Northeastern Brazilian coastal communities, who use it as food, source of income and cultural reference. The extractivism and marketing of this crustacean is essential for the socio-economic development of the states of Maranhão, Piauí and Ceará. The aim of this study was to carry out the monitoring of harvesting and landing of the mangrove crab in Ilha Grande, PI. Interviews were conducted with crab gatherers and transporters to obtain information about harvesting, landed volume, market price and destination of commercialized crab. The main capture spots were located at the Maranhão part of the Parnaíba River Delta. Crab gatherers are active 5.07 times a week and spend an average of 6 hours in mangrove. The average number of crabs collected per gatherer/day was 77.0. The quantity landed in daytime period was 63,628 crabs/month, totalizing 714,543 crabs/year. The average price traded was USD 0.19/crab. The production chain of mangrove crab harvesting requires planning for maintain the natural stocks and aggregation of value to the product, benefiting the appreciation of crab gatherers.